2013
DOI: 10.1111/nep.12124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolic syndrome on clinical outcomes of non‐diabetic peritoneal dialysis patients in India

Abstract: Prevalence of MS in non-diabetic PD patient is high and predicts long term patient and technique survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…However, although also from Taiwan and using the same NCEP-ATPIII definition, Liao et al [17] found that incident nondiabetic PD patients ( n = 280) with MS had poorer patient survival compared to those without MS for both total and cardiovascular event–free patient survival. Similarly, higher patient mortality was found in the nondiabetic Indian PD patients with MS compared to those without ( n = 163) [18] . Sample size variation may be an explanation for the different conclusions.…”
Section: Controversies About Ms In Pd Patientsmentioning
confidence: 79%
See 1 more Smart Citation
“…However, although also from Taiwan and using the same NCEP-ATPIII definition, Liao et al [17] found that incident nondiabetic PD patients ( n = 280) with MS had poorer patient survival compared to those without MS for both total and cardiovascular event–free patient survival. Similarly, higher patient mortality was found in the nondiabetic Indian PD patients with MS compared to those without ( n = 163) [18] . Sample size variation may be an explanation for the different conclusions.…”
Section: Controversies About Ms In Pd Patientsmentioning
confidence: 79%
“…In Taiwan, Liao et al [17] found that the prevalence was 52.9% among all PD patients, and it was 39.4% when diabetics were excluded. However, Prasad et al [18] reported 51.3% among nondiabetic PD patients. Therefore, there is substantial variation between countries and ethnicity, but the overall impression is that the prevalence is substantially higher than that in the general population even when diabetics are excluded.…”
Section: Prevalence Of Ms In Pd Patientsmentioning
confidence: 96%
“…A recent meta-analysis of eight studies with a total of 1273 ESRD patients demonstrated that patients with MetS have a higher risk of all-cause mortality compared to patients without metabolic syndrome [10]. However, these studies comprised mostly of Asian HD patients [11,12,13] and patients on peritoneal dialysis [14,15,16]. Only two prospective studies [17,18] investigated mortality in Caucasian HD patients with MetS.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of death due to cardiovascular disease reaches 40-50% in patients receiving renal replacement therapies 4 . Several studies have showed that peritoneal dialysis patients were more at risk for the development of dyslipidemia and hyperinsulinemia 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%